CAN CEO POWER MODERATE THE INFLUENCE OF INTERNET FINANCIAL REPORTING ON MARKET REACTIONS? - Aristanti Widyaningsih; Tiara Oksari (JRAK, 2023)
This research aims at determining the effect of Internet financial reporting and CEO power on market reactions and how CEO power moderates the effect of Internet financial reporting on market reactions. The research method used a quantitative approach and the sampling used a purposive sampling method to obtain 126 manufacturing sector companies listed in Indonesia. In addition, the analytical method used Moderated Regression Analysis. The test results showed that Internet financial reporting has no significant effect on market reactions, CEO power significantly affects market reactions, but CEO power could not strengthen the influence of Internet financial reporting on market reactions. The practical implications of the research results showed that Internet financial reporting helps investors obtain valuable information for decision-making.